What’s new in diagnostics and therapy of pulmonary embolism? - Zawilska, Krystyna (Przewodnik Lekarza/Guide for GPs, 2009)
Because of the great variability and lack of specificity of symptoms of pulmonary embolism (PE) only up to 30% of cases are diagnosed during life. It also often remains unrecognized even at death due to lack of routine postmortem examination. These factors result in marked underestimation of the PE incidence. The VITAE (Venous Thrombo-Embolism Impact Assessment Group in Europe) estimated the annual number of PE events in 2004 across 25 EU countries to measure up to 435,000 cases. Extrapolating the VITAE model, about 37,000 symptomatic PE events occur yearly in Poland alone. The ENDORSE study, a cross-sectional survey of nearly 70,000 patients hospitalized in 32 countries, has shown that 64% of surgical patients and 42% of medical patients would benefit from antithrombotic prophylaxis. In Polish hospitals only 66% of surgical and 35% of medical patients who would benefit receive the proper antithrombotic prophylaxis. The purpose of this article is to focus on currently available and validated methods of diagnosis, prognostic evaluation (novel stratification of patients into high and non-high risk PE) and to discuss appropriate therapy for PE. It summarizes data published in 2008 by the European Society of Cardiology as guidelines of diagnosis and management of acute PE and reviews the practice guidelines for antithrombotic and thrombolytic therapy published in the same year by the American College of Chest Physicians. The potential of a new anticoagulant drug, the indirect factor Xa inhibitor fondaparinux, for therapy of PE is also discussed. Therapeutic features of warfarin, which is now also available in Poland, are compared to those of acenocoumarol.